Abundance and ecological footprint of Pseudoalteromonas phage vB_PhoS_XC in the Ulva prolifera green tide - Sun, Jianhua; Zhang, Xinran; Liang, Yantao; Zheng, Kaiyang; Kennedy, Fraser; Han, Meiaoxue; Liu, Gang; Liu, Yundan; Wang, Ziyue; Chen, Xuechao; Sung, Yeong Yik; Mok, Wen Jye; et al. (Frontiers in Marine Science, 2023)
Pseudoalteromonas is a ubiquitous and abundant genus of marine bacteria commonly associated with algae. In this study, a novel siphoviral-morphological bacteriophage, vB_PhoS_XC, was isolated from the coastal seawaters of Qingdao (China) during a bloom of the Ulva prolifera (U. prolifera) green tide. The morphology of this phage (icosahedron head 51 ± 1 nm in diameter; a tail length of 86 ± 1 nm) was characterized through transmission electron microscope. The biological properties of this virus showed a short latent period (45 minutes), a large burst size (241 virions per cell) and a relatively wide range of temperatures/pH level tolerance (-20°C to 45°C and pH 4 to pH 10, respectively). The vB_PhoS_XC has a 46,490-bp double-stranded DNA genome with a G+C content of 40.0%, and encodes 72 open reading frames (ORFs). Thirty-five of these ORFs were assigned into known functions based on BLAST-based algorithm against NR database of GenBank. In addition, eco-genomic analysis provides the evidence of vB_PhoS_XC accompanied by bloom of U. prolifera, and confirmed the high expression of two phosphatase-metabolism-related auxiliary metabolic genes (AMGs). This study provides new insights into the functional and ecological roles of the Pseudoalteromonas phage vB_PhoS_XC, shedding light on the virological study approach combined with traditional isolation and meta-omics data.